SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

People modify their tutoring behavior in robot-directed interaction for action learning - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fischer, Kerstin; Nagai, Yukie; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning, 2009. ICDL 2009. IEEE 8th International Conference on Development and Learning)
In developmental research, tutoring behavior has been identified as scaffolding infants' learning processes. It has been defined in terms of child-directed speech (Motherese), child-directed motion (Motionese), and contingency. In the field of developmental robotics, research often assumes that in human-robot interaction (HRI), robots are treated similar to infants, because their immature cognitive capabilities benefit from this behavior. However, according to our knowledge, it has barely been studied whether this is true and how exactly humans alter their behavior towards a robotic interaction partner. In this paper, we present results concerning the acceptance of a robotic agent in a social learning scenario obtained via comparison to adults and 8-11 months old infants in equal conditions. These results constitute an important empirical basis for making use of tutoring behavior in social robotics. In our study, we performed a detailed multimodal analysis of HRI in a tutoring situation using the example of a robot simulation equipped with a bottom-up saliency-based attention model. Our results reveal significant differences in hand movement velocity, motion pauses, range of motion, and eye gaze suggesting that for example adults decrease their hand movement velocity in an Adult-Child Interaction (ACI), opposed to an Adult-Adult Interaction (AAI) and this decrease is even higher in the Adult-Robot Interaction (ARI). We also found important differences between ACI and ARI in how the behavior is modified over time as the interaction unfolds. These findings indicate the necessity of integrating top-down feedback structures into a bottom-up system for robots to be fully accepted as interaction partners.
Keywords: robot simulation; hand movement velocity; robotic interaction partner; robotic agent; robot-directed interaction; multimodal analysis; Motionese; Motherese; intelligent tutoring systems; immature cognitive capability; human computer interaction; eye gaze; child-directed speech; child-directed motion; bottom-up system; bottom-up saliency-based attention model; adult-robot interaction; adult-child interaction; adult-adult interaction; human-robot interaction; action learning; social learning scenario; social robotics; software agents; top-down feedback structures; tutoring behavior

A Language for the Rapid Prototyping of Mobile Evolving Agents - Müller, Wolfgang; Meyer, A.; Zabel, Henning (Proceedings of the 34th Annual Hawaii International Conference on System Sciences)
This article presents SAL, a general purpose scripting language for the rapid development of distributed software agents seamlessly embedded in a visual environment. Integrated facilities for dynamic visualization provide sample but powerful means for debugging and domain-oriented animation. SAL agents are arranged on a set of 2D worksheets which can be distributed over different machines. An agent's program is defined by the means of a table specifying a set of state transition rules with a condition and a sequence of actions each. Beyond basic computation and communication, actions can dynamically modify the agent's depiction, its program, and spawn arbitrary processes. A couple of examples demonstrate SAL's applicability in various domains like electronic systems design and process management.
Keywords: software prototyping; distributed programming; authoring languages; software agents; program visualisation; parallel languages